200k views
0 votes
Solve the following equation:

x + √(x+3) = 3 + 3√(1-x)

1 Answer

3 votes

Answer:


x+√(x+3)=3+3√(1-x)


Remove~ Square ~root


-36x^3+252x^2-540x+324=


x^4-32x^3+286x^2-480x+225


Now ~\mathrm{Switch\:sides}


x^2-6x√(-x+1)-15x+18√(-x+1)+18=x+3


\mathrm{Subtract\:}x^2-15x\mathrm{\:from\:both\:sides}


x^2-6x√(-x+1)-15x+18√(-x+1)+18-\left(x^2-15x\right)=


x+3-\left(x^2-15x\right)


New ~Simplify


-6x√(-x+1)+18√(-x+1)+18=-x^2+16x+3


Subtract ~18~ from ~ both~ sides


-6x√(-x+1)+18√(-x+1)+18-18=-x^2+16x+3-18


Simplify


-6x√(-x+1)+18√(-x+1)=-x^2+16x-15


Now~ factor:


-6x√(-x+1)+18√(-x+1)(-x+3)


6√(-x+1)\left(-x+3\right)=-x^2+16x-15


Solve~~-36x^(3)+252x^(2) -540x+324=x^(4) -32x^(3) +286x^(2) -480x+225=


x=1,\:x=-3

-----------------------

hope it helps..

have a nice day/night

User Mathieu Schaeffer
by
4.9k points